Knowledge, practices, and perceptions towards malaria prevention and control among Residents of Canaanland and surrounding areas in Ota, Ogun State, Nigeria: a cross-sectional study - Wakai, Theophilus; Fiamitia, Carrin; Kintung, Irrinus; Johngwe, Mac; Chinedu, Shalom; Afolabi, Israel (Frontiers in Tropical Diseases, 2025)
IntroductionMalaria remains a major public health concern in Nigeria, accounting for approximately 27% of global cases. In Ota, Ogun State, a recent study reported a 44% prevalence among symptomatic patients. This high burden underscores the importance of understanding community knowledge, attitudes, and behaviors, which are critical for designing targeted and effective control strategies.MethodsA cross-sectional study was conducted between March and June 2025 among 483 residents of Canaanland, a semi-urban religious and educational community. Data were collected anonymously using semi-structured questionnaires in both hardcopy and KoboToolbox formats, with manual entry for paper responses. Descriptive analysis was performed using R software (version 4.3.1).ResultsOverall, 55% of respondents had moderate malaria knowledge, 60% exhibited poor preventive practices, and 75.8% believed malaria can be eliminated. Most respondents (80.5% students) demonstrated high awareness (98.0%), yet misconceptions about malaria causes (e.g., dirty water, contaminated food) persisted. Insecticide-treated net (ITN) use was suboptimal, with only 27.7% using ITNs nightly despite 66.9% ownership; postgraduate students were less likely to use ITNs. Preventive practice and attitude scores were significantly associated with gender and education (p < 0.05), with males and undergraduates exhibiting more suboptimal behaviors. While 67.7% sought prompt treatment, nearly one-quarter relied on self-diagnosis. More than half rated government malaria control efforts poorly, yet the majority supported increased sensitization. Key barriers identified included poor sanitation, limited ITN access, and financial constraints.DiscussionThese findings highlight that higher education alone does not ensure effective malaria-related behaviors. Persistent misconceptions, poor preventive practices, and systemic barriers call for behavior-focused, context-specific interventions alongside awareness campaigns in educated, semi-urban communities.